The effects of biotic stress on the sexual reproduction process of flowering plants - Zhenzhen Li; Shuo Wang; Yike Wang; Hongxia Zhang; Lu Liu; Shiwen Su; Sue Lin (PeerJ)
The sexual reproduction phase of flowering plants encompasses a multitude of physiological processes, including floral induction, floral organ morphogenesis, fertilization, and the maturation of seeds and fruits. In addition to being vital to the successful reproduction of the plants, these processes are also crucial to their adaptation to diverse environmental conditions. However, this phase is extremely complex and vulnerable to environmental impacts and constraints, with both biotic and abiotic stresses playing a significant role. Accumulating evidence has demonstrated that environmental stress has multifaceted impacts on plant sexual reproduction, leading to substantial losses in seed production and crop yield. Although several excellent reviews have explored the regulatory mechanisms of abiotic stresses (such as light and temperature stress) on the plant sexual reproduction process, particularly flowering time and gametophyte development, a comprehensive overview of the effects of biotic stresses is still lacking. Rather than comprehensively reviewing the massive amount of literature in this field, our review aims to leverage case studies to cover a wide range of mechanisms by which biotic stressors, including fungi, bacteria, viruses, parasitic plants, and herbivorous animals, affect the sexual reproduction process of flowering plants.